Behavior Therapy and Modelo Latinoamérica; Assembling and Demarcating Psychology in Colombia - Mora-Gámez, Fredy A; Grupo de Estudios Sociales de la Ciencia, la Tecnología y la Medicina, Universidad Nacional de Colombia (2014)
The set of psychological techniques known as Behavior Therapy is reframed as a sociotechnical device and its circulation from the US to Colombia in the 1970s is reconstructed. The circulation of Behavior Therapy is described in academic spaces such as Universidad Nacional de Colombia and Universidad Javeriana. The possibility of Behavior Therapy as a Boundary Object as a mean for demarcation from psychiatry, and as a way for promoting and mobilizing scientific discourses about subjectivity. Thus, a relation between the training guidelines for psychology curricula known as Modelo Latinoamérica and the assemblage of Behavior Therapy is outlined. Finally, some considerations for future interdisciplinary research on the history of psychology are proposed.